On the origin and diversification of the stygobiotic freshwater snail genus Hauffenia (Caenogastropoda: Hydrobiidae) with special focus on the northern species and the description of two new species - Haase, Martin; Grego, Jozef; Erőss, Zoltán Péter; Farkas, Roland; Fehér, Zoltán (European Journal of Taxonomy, 2021)
During systematic surveys of groundwater snails in Slovakia, Hungary and Bosnia and Hercegovina two new species of the genus Hauffenia, H. lozekiana sp. nov. from a single locality in Slovakia, and H. steffeki sp. nov. with a small range in Bosnia and Hercegovina were discovered and are here described based on shell morphology, anatomy and DNA sequence data (COI, 16S rRNA, ITS2). The discovery of H. steffeki sp. nov. extends the range of the genus considerably towards the south. Hauffenia lozekiana sp. nov. appears to be a relict surviving within the range of the today widely distributed H. kissdalmae. Based on a time tree, we developed a scenario for the origin and diversification of the genus. The ancestor probably evolved in the Miocene on the Balkans and with the gradual desiccation of the Paratethys and its remnant water bodies diversified towards the north. Karstic and in particular alluvial connectivities together with changing courses of paleo-rivers probably played an important role for dispersal. Ecological observations suggest that the phreatic rhizosphere, the delicate net of tree rootlets and their exudates, are important for the existence of these groundwater snails.